Immune and Inflammation in Acute Coronary Syndrome: Molecular Mechanisms and Therapeutic Implications - Haiming Wang; Zifan Liu; Junjie Shao; Lejian Lin; Min Jiang; Lin Wang; Xuechun Lu; Haomin Zhang; Yundai Chen; Ran Zhang (Journal of Immunology Research)
Acute coronary syndrome (ACS) is a major cause of acute death worldwide. Both innate and adaptive immunity regulate atherosclerosis progression, plaque stability, and thrombus formation. Immune and inflammation dysfunction have been indicated in the pathogenesis of ACS. The imbalance in the proatherogenic and antiatherogenic immune networks promotes the transition of plaques from a stable to unstable state and results in the occurrence of acute coronary events. The residual inflammatory risk (RIR) has received increasing attention in recent years, and lowering RIR has been expected to improve the outcomes of ACS patients. The CANTOS, COLCOT, and LoDoCo trials verified the benefits of reducing cardiovascular events using anti-inflammation therapies; however, most of the other studies focusing on lowering RIR produced negative or contradicting results. Therefore, restoring the balance in autoimmune regulation is essential because proatherogenic and antiatherogenic immunomodulatory effects are equally important in the complex human immune network. In this review, we summarized the recent evidence of the roles of proatherogenic and antiatherogenic immune networks in the pathogenesis of ACS and discussed how immune and inflammation contribute to atherosclerosis progression, plaque instability, and adverse cardiovascular events. We also provide a “from bench to bedside” perspective of a novel and promising personalized strategy in RIR intervention and therapeutic approaches for the treatment of ACS.